2023
DOI: 10.1111/head.14528
|View full text |Cite
|
Sign up to set email alerts
|

A head‐to‐head observational cohort study on the efficacy and safety of monoclonal antibodies against calcitonin gene–related peptide for chronic and episodic migraine

Abstract: Objective: To compare the effectiveness and safety of galcanezumab, fremanezumab, and erenumab for the treatment of chronic and episodic migraine, through real-world data.Background: Monoclonal antibodies (mAbs) targeting the calcitonin gene-related peptide (CGRP) pathway have been tested extensively in several clinical trials for both episodic and chronic migraine, showing high effectiveness, safety, and tolerability; however, there are no prospective real-world studies intending to compare their efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…All three CGRP medications decreased MDM in responders with large effect sizes. This finding is consistent with clinical trials, systematic reviews, and meta‐analyses of clinical trials 29–33 and complements recent work 61,62 . At both follow‐ups, a higher baseline MDM was associated with a greater decrease in MDM at follow‐up and greater decreases in MDM at follow‐up were seen in females and in patients with longer duration of follow‐up.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All three CGRP medications decreased MDM in responders with large effect sizes. This finding is consistent with clinical trials, systematic reviews, and meta‐analyses of clinical trials 29–33 and complements recent work 61,62 . At both follow‐ups, a higher baseline MDM was associated with a greater decrease in MDM at follow‐up and greater decreases in MDM at follow‐up were seen in females and in patients with longer duration of follow‐up.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with clinical trials, systematic reviews, and meta-analyses of clinical trials [29][30][31][32][33] and complements recent work. 61,62 At both follow-ups, a higher baseline MDM was associated with a greater decrease in MDM at follow-up and greater decreases in MDM at follow-up were seen in females and in patients with longer duration of follow-up. Patients with a prior hospitalization for migraine and non-response to a greater number of previously tried preventives showed a smaller decrease in MDM at the first, but not the second, follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…In a prospective study involving 140 migraineurs (45 treated with erenumab, 54 with fremanezumab, and 41 with galcanezumab), the authors reported no differences in migraine frequency, MIDAS, or symptomatic medication intake. Interestingly, fremanezumab and galcanezumab in chronic migraineurs with MOH were superior to erenumab [21].…”
Section: Discussionmentioning
confidence: 97%
“… 13 Other groups however, have reported lower rates. 15 The reason for such variability in continuation rates is not clear.…”
Section: Discussionmentioning
confidence: 99%